PENERAPAN MODIFIKASI PERMAINAN SEPAK BOLA TERHADAP MINAT SISWA PUTRI DALAM PEMBELAJARAN SEPAK BOLA DI KELAS VIIIC SMPN 5 PALU - Ratna Djafar; Gunawan; Mursid Amorokhman (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Learning activities especially in teaching football games which is done by State Junior High School in Palu students in Palu, the male students are more dominant and enthusiastic when practiced football, while the female students are less active and didn’t pay attention to the teacher when learning activities are in progress. These problems aren’t appropriate because it happens in learning physical of education activities which all of the students should be more active and focus in football subjects. In the other hand the female students are afraid when they accepted the ball which is too fast and hard. In general studies the teacher usually uses a common football subject which is made female students less interest in learning football. The purpose of this research is to know how much the influence when applied the modification football games to increase female students’ interest in football learning activity (a study for students grade VIIIC in State Junior High School 5 Palu). This research include in experimental research and used one group pre test and post test design, the researcher take the sample with gather all of the students in class VIIIC 5 Palu, where the sample of this research all student in class VIIIC SMPN 5 Palu, for about 35 students which is 18 female students from VIIIC and 17 female students from Class VIIID. The instrument which is used in this research is filling the questionnaire about students’ interest which contain of 19 questions taken from Arvan Yahya Sulthoni’s previous research. The result and calculation from this research used SPSS (Statistical Package for the Social Science) it knows that the average of pre test questionnaire is 65,60%. Otherwise the average of post test questionnaire is 69,83%. According to the result of this research, an application of modification football games to increase female students’ interest in football learning activity is increase 6,45%.